PENGEMBANGAN INSTRUMEN EVALUASI BELAJAR COMPUTER BASED INTRUCTION (CBI) DENGAN MODEL DRILL INTERAKTIF SEBAGAI PROSES EVALUASI BELAJAR PADA MATA PELAJARAN SISTEM KOMPUTER - Nuriati July; Muhammad Amin (Journal of Electrical Vocational Teacher Education (JEVTE), 2022)
AbstractThis research aims to find out how the development of computer based instruction (cbi) evaluation instruments with interactive drill models of computer system subjects in vocational schools and the feasibility of using computer based instruction (cbi) learning evaluation instruments with interactive drill models of computer system subjects in smk. This research was conducted on students of class X Majoring in Computer Engineering and Private Vocational Network Citra Abdi Negoro. Media development procedures are carried out by Research and Development methods or better known as R&D and use analysis design models, design, development, implementation and evaluation (ADDIE) but in the development of this research is limited at the implementation stage. Based on the data obtained during the study, validation results from the content expert get a final interpretation of (5,72) with very feasible criteria. Validation results from media experts get a final interpretation of (3,83) with decent criteria. In small group trials it was 82.20% and in large group trials it was 89.04%. From the practicality assessment obtained from the student's response to small and large group trials have the category "Excellent". The percentage of effectiveness gets an average of 0.86 with a high category. Thus the computer based intruction (cbi) learning evaluation instrument with this interactive drill model is feasible and effective to use and received positive responses from validator experts and users.Key Words: learning evaluation instruments, computer based intruction, interactive drill. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana pengembangan instrumen  evaluasi belajar computer based instruction (cbi) dengan model drill interaktif mata pelajaran system computer di smk dan kelayakan serta kepraktisan penggunaan terhadap instrumen evaluasi belajar computer based instruction (cbi) dengan model drill interaktif mata pelajaran system computer di smk. Penelitian ini dilakukan pada siswa kelas X Jurusan Teknik Komputer dan Jaringan SMK Swasta Citra Abdi Negoro. Prosedur pengembangan media dilakukan dengan metode Research and Development atau lebih dikenal dengan R&D dan menggunakan model desain pengembangan Analysis, Design, Development, Implementation and Evaluation (ADDIE) tetapi pada pengembangan penelitian ini dibatasi pada tahap implementation. Berdasarkan data yang didapat selama penelitian, Hasil validasi dari ahli isi/konten mendapatkan interpretasi akhir sebesar (5,72) dengan kriteria sangat layak. Hasil validasi dari ahli media mendapatkan interpretasi akhir sebesar (3,83) dengan kriteria layak. Pada uji coba kelompok kecil sebesar 82,20% dan pada uji coba kelompok  besar sebesar 89,04%. Dari penilaian kepraktisan yang diperoleh dari respon siswa pada uji coba kelompok kecil dan besar mempunyai katagori “Sangat Baik”. Persentase kefektifan mendapatkan rata-rata 0,86 dengan kategori tinggi. Dengan Demikian instrumen evaluasi belajar computer based intruction (cbi) dengan model drill interaktif ini layak dan efektif digunakan serta mendapat tanggapan positif dari para ahli validator dan pengguna.Kata Kunci : instrumen evaluasi belajar, computer based intruction, drill interaktif